Risk Assessment in Lifting Steel Pipes with Overhead Cranes using Fault Tree Analysis Combined with Failure Modes and Effects Analysis: A Case Study of Steel Pipe Manufacturing Factory - ภู่งาม มุขตาภา; สอนวงษ์ พิพัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to analyze the risks associated with the use of lifting equipment for steel pipe handling with overhead cranes in a ductile iron pipe manufacturing plant. The study applies a systems-based risk assessment approach using Fault Tree Analysis (FTA) and Failure Modes and Effects Analysis (FMEA), with the objectives of identifying hazards, assessing risks, and proposing appropriate risk management measures in the lifting and handling process. Data were collected through purposive sampling by interviewing 37 employees directly involved in the lifting and handling operations. Additionally, 20 direct field observations were conducted by the researcher, alongside a review of the plant’s internal accident statistics. These data were analyzed using FTA to identify key failure points that contribute to system breakdowns, which were subsequently quantified through FMEA. The analysis revealed high-risk failure modes, notably the incorrect installation of shackles (RPN = 210) and hook fractures due to improper lifting angles (RPN = 200). The findings were consistent with OSHA’s accident database, relevant Thai safety regulations, and international standards, particularly concerning the proper use and pre-use inspection of lifting equipment. Based on the results, the study proposes several measures to enhance safety in steel pipe lifting and handling operations. These include training and upskilling of lifting personnel, regular inspection and maintenance of lifting equipment, and the adoption of technology to improve control and accident prevention. This research contributes to the advancement of knowledge in industrial risk management and offers practical guidance that can be adapted to other types of manufacturing facilities in the future.